2017
DOI: 10.18632/oncotarget.22215
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease is associated with a risk of higher mortality following total knee arthroplasty in diabetic patients: a nationwide population-based study

Abstract: Diabetes and chronic kidney disease (CKD) are associated with a higher rate of complications in patients undergoing total knee arthroplasty (TKA). The purpose of this study was to determine the effects of CKD and diabetes in patients after TKA. Diabetic patients who received unilateral primary TKA between January 2008 and December 2011 were enrolled. The follow-up period was more than 6 months. The primary outcome was a TKA-related infection and the secondary outcome was all-cause mortality. The study cohort i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
(32 reference statements)
2
26
1
Order By: Relevance
“…These patients were then classified into three groups according to renal functional status: those with no CKD (non‐CKD group), those with CKD (CKD group), and those receiving dialysis (dialysis group). CKD was defined according to the ICD‐9‐CM diagnostic codes validated in previous studies, as given in Supplementary Table S1 . Under the regulation of the Taiwan NHI, the diagnosis of CKD was based on the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF‐K/DOQI) guidelines: (1) the appearance of indicators of kidney damage in the urine or blood, and (2) estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These patients were then classified into three groups according to renal functional status: those with no CKD (non‐CKD group), those with CKD (CKD group), and those receiving dialysis (dialysis group). CKD was defined according to the ICD‐9‐CM diagnostic codes validated in previous studies, as given in Supplementary Table S1 . Under the regulation of the Taiwan NHI, the diagnosis of CKD was based on the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF‐K/DOQI) guidelines: (1) the appearance of indicators of kidney damage in the urine or blood, and (2) estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Surgery‐related infections were defined as all instances of superficial wound infection or deep infection during the follow‐up period. Concerning the subtype of infection, superficial wound infection was defined as readmission based on an infection requiring only antibiotic treatment; deep infection included readmission for simple debridement and surgical debridement with implant removal …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported correlation between CKD and TJA outcomes. Reports from earlier studies vary with regard to the effect of CKD on the risk of complications, such as mortality, PJI, and arthroplasty revision rate [15,[21][22][23][24][25][26]. However, no systematic review or meta-analysis of this relationship was conducted.…”
Section: Introductionmentioning
confidence: 99%